Role of Flavonoids in the Interactions among Obesity, Inflammation, and Autophagy - María José García-Barrado; María Carmen Iglesias-Osma; Elena Pérez-García; Sixto Carrero; Enrique J. Blanco; Marta Carretero-Hernández; José Carretero (MDPI AG, 2020)
Nowadays, obesity is considered as one of the main concerns for public health worldwide, since it encompasses up to 39% of overweight and 13% obese (WHO) adults. It develops because of the imbalance in the energy intake/expenditure ratio, which leads to excess nutrients and results in dysfunction of adipose tissue. The hypertrophy of adipocytes and the nutrients excess trigger the induction of inflammatory signaling through various pathways, among others, an increase in the expression of pro-inflammatory adipocytokines, and stress of the endoplasmic reticulum (ER). A better understanding of obesity and preventing its complications are beneficial for obese patients on two facets: treating obesity, and treating and preventing the pathologies associated with it. Hitherto, therapeutic itineraries in most cases are based on lifestyle modifications, bariatric surgery, and pharmacotherapy despite none of them have achieved optimal results. Therefore, diet can play an important role in the prevention of adiposity, as well as the associated disorders. Recent results have shown that flavonoids intake have an essential role in protecting against oxidative damage phenomena, and presents biochemical and pharmacological functions beneficial to human health. This review summarizes the current knowledge of the anti-inflammatory actions and autophagic flux of natural flavonoids, and their molecular mechanisms for preventing and/or treating obesity.